BEDAH MAKNA, UNSUR DAN ASPEK IJAZ AL-QURAN - Atila Nurkhatiqah; Camelia Fitri; Dhiya Rahmatina (CV. Adiba Aisha Amira, 2022)
Al-Quran as the greatest revelation as well as functioning as a guide to life that must be believed and guided, contains Islamic treatises, implied also amazing wisdom called miracles. When the term i'jaz was attached to the Koran, it demanded that the Holy Book brought by the Messenger of Allah be able to subdue all the writings that ever existed, while also crowning the Koran as the most noble and undeniable book. But how to understand the i'jaz of the Qur'an with the state of the Qur'an that has been in our hands all this time. This paper invites to know the meaning, elements and aspects of i'jaz in the Al-Quran